Extreme cases and the criminal justice system: responses to a traumatic sexual assault in India - Kadyan, Sneha (International journal of comparative and applied criminal justice, 2017)
This paper addresses criminal justice responses that came on the heels of a traumatic sexual assault in public space in India. The incident referred to as “Nirbhaya,” drew attention to the nation as well as the world the violence against women who on the one hand find themselves in public spaces designed for all denizens in this globalised world, yet, subject to sexploitation and devoid of safeguards and equal protection. In this paper we catalogue modifications to Indian criminal justice as a result of the Nirbhaya case to illustrate how extreme events help drive changes to the system in a large democracy, yet an economically developing one. More specifically, we address changes that have been incorporated in criminal laws, police procedures, and crime prevention efforts, as well as assess the degree to which these efforts have been effective.